Asset price changes, external wealth and global welfare - Timothy Andreas Meyer (Kiel Institute for the World Economy (IfW Kiel), 2024)
U.S. equity outperformance and sustained dollar appreciation have led to large valuation gains for the rest of the world on the U.S. external position. The author constructs their global distribution, carefully accounting for the role of tax havens. Valuation gains are concentrated and large in developed countries, while developing countries have been mostly bypassed. To assess the welfare implications of these capital gains, the author adopts a sufficient statistics approach. In contrast to the large wealth changes, most countries so far did not benefit much in welfare terms. This is because they did not rebalance their portfolios and realize their gains, while they were further hurt by rising import prices from the strong dollar.
Keywords: F21; F32; F40; G15; 330; Foreign Assets; Global Imbalances; Valuation Effects